The Perceptions on breast cancer: a study on nuns in Manggarai - Wea, Lidwina Dewiyanti (Jurnal Kesehatan, 2021)
This study collect information on nuns in Manggarai whom categorized as nulliparity. 6 nuns are participated on this research. Qualitative study were used to browse themes related to the perception on breast cancer. Data were collected using interview recorded with voice recorder. Study findings emphasized several important facts that influencing their behavior on giving opinion of breast cancer. There were 4 themes obtained. First theme was the lack of knowledge. The theme represented by the findings that the majority of the participant could not answer the question on definition, etiology, sign and symptom, and the cancer treatment. The second theme was belief. Majority of participant belief that they could not possibly suffer from breast cancer because they are unmarried and their life style within the monastery is being maintain better. The third theme was the habituality. The statement supporting this theme was within the monastery there were no discussion on reproductive health, they thought that the said discussion was not the priority on the monastery life. The fourth theme was hope. This theme was appear as the majority of participant wished for the health education on reproductive health especially on breast cancer. Thus, the findings on this research explain that the participants had not yet obtained the proper information of breast cancer. Belief and habits orelated to breast cancer also appear in the study findings, that also related to culture and custom going on for a long period of time. Wishful response stated by participants was the findings need to be noticed by all involved stakeholder. Participant needed the accurate information on reproductive health specifically, breast cancer.